2002
DOI: 10.1111/j.1365-2621.2002.tb10279.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Application of Dietary Fiber and Cellulose from Pineapple Cores

Abstract: Pineapple core dietary fiber (PDF) was obtained by alcoholic extraction; pineapple core cellulose (PC) was a product of alkali extraction with a bleaching process. Total dietary fiber content of PDF and PC was 99.8% and 95.2% (dry basis), respectively, and their water activity was 0.25. PC contained 91.2% cellulose with a pH value of 4.0, while that of PDF was 6.2. The fiber product with large particle size gave higher values than the product with smaller particles for pH, water and oil retention capacity, set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 8 publications
5
35
0
1
Order By: Relevance
“…Ramirez and de Delahaye, [30] reported similar study and due to its hydration properties and flavor, pineapple flour was recommended in the preparation of crackers and as ingredients in desserts. Similar observations were reported for good sensory functions for pineapple core fiber incorporated in cake-type doughnuts, golden layer cake and beef burgers [23]. Notably, Sreenath et al, [24] reported that sensory quality evaluation for Ananas camosus pineapple flour incorporated in sponge cakes had similar acceptability to control sponge cakes, which is similar to that reported for cakes incurporated with OSPS in this study.…”
Section: Water Activity Total Soluble Solids and Ph Measurements Of supporting
confidence: 78%
See 1 more Smart Citation
“…Ramirez and de Delahaye, [30] reported similar study and due to its hydration properties and flavor, pineapple flour was recommended in the preparation of crackers and as ingredients in desserts. Similar observations were reported for good sensory functions for pineapple core fiber incorporated in cake-type doughnuts, golden layer cake and beef burgers [23]. Notably, Sreenath et al, [24] reported that sensory quality evaluation for Ananas camosus pineapple flour incorporated in sponge cakes had similar acceptability to control sponge cakes, which is similar to that reported for cakes incurporated with OSPS in this study.…”
Section: Water Activity Total Soluble Solids and Ph Measurements Of supporting
confidence: 78%
“…The amount of protein, fat and ash of OSPS varied significantly among the three pineapple varieties ( Table 2). The proximate values of OSPS compared similarly with other fruits syrups and flours as reported for dehydrated soursop, guava and pineapple [30], pineapple core [23] and waste pulp pineapple [24]. Vitamin C which is important for wellness was significantly abundant in Sugar laof (2.61 mg/100g) compared to Smooth cayenne (2.52 mg/ 100g) and MD2 (2.25 mg/100g).…”
Section: Water Activity Total Soluble Solids and Ph Measurements Of supporting
confidence: 49%
“…Bulk and packed density of WB was determined according to the method described by Prakongpan et al (2002).…”
Section: Bulk and Packed Densitymentioning
confidence: 99%
“…The bulk density determination was based on the methodology presented by Prakongpan et al (2002). A preweighed graduated cylinder was filled with 50 mL of sample and was gently vibrated during 2 s. The volume was recorded, the cylinder content was weighed and the density was apparent expressed as mass per volume.…”
Section: Bulk Densitymentioning
confidence: 99%